Decreased Activity and Genetic Polymorphisms of CYP2C19 in Behçet's Disease. Issue 4 (6th September 2017) - Goktas, Mustafa Tugrul; Karaca, Ragip Ozgur; Kalkisim, Said; Cevik, Lokman; Kilic, Levent; Akdogan, Ali; Babaoglu, Melih O.; Bozkurt, Atilla; Bertilsson, Leif; Yasar, Umit
Abstract: Behçet's disease (BD) is a systemic autoimmune disorder. Cytochrome P450 enzymes (CYPs) are responsible for various drug metabolism reactions as well as those of endogenous substances which may be associated with autoimmune disease susceptibility. Recently, we reported that in patients with BD, CYP2C9 seems to be down‐regulated due to inflammation. In the same Turkish patients with BD, we investigated whether also CYP2C19 activity is decreased. Lansoprazole (30 mg) was given as a probe drug to evaluate CYP2C19 activity in 59 patients with BD and 27 healthy control volunteers. An HPLC method was used to determine plasma lansoprazole and its metabolite, 5‐hydroxy lansoprazole, concentrations. The genotyping for CYP2C19 *2, *3 and *17 polymorphisms was made using PCR‐RFLP. The median lansoprazole/5‐hydroxy lansoprazole metabolic ratio (MR) in patients with BD was 2.6‐fold higher as compared to the healthy control group ( p = 0.001, 22.6 (1.3–26) and 8.8 (0.5–140) as median and range, respectively). The CYP2C19*17*17 genotype frequency was found to be significantly less in the BD group as compared to the healthy controls (1.7% versus 14.8% in controls, p = 0.01). Additionally, colchicine treatment did not affect the CYP2C19 enzyme activity in six patients ( p = 0.43). In conclusion, the patients with BD had lower CYP2C19 enzyme activity and lower frequency of the CYP2C19*17 allele as compared to those of the healthy controls. Further studies are warranted on the mechanisms underlying this relation. This study should also be applied to other autoimmune diseases similarly characterized by local or systemic inflammation.